Community re-entry program on global functioning and medication adherence among bipolar affective disorder patients- A randomized controlled trial pilot study - Jaishri; Sreevani Rentala; Preethy Kathiresan; Mukesh Swami (Journal of Education and Health Promotion)
Background: The Community re-entry program aims to train participants with the skills and information and help to move efficiently through the mental health in-patient setting to more independent living in the community. This quantitative study to explores the effectiveness of community re-entry program on global functioning and medication adherence for patients with bipolar affective disorder. Material and Methods: The study was a randomized controlled clinical trial and conducted by the Consolidated Standards of Reporting Trials (CONSORT) 2010 guidelines. The present study was done at the in-patient department of the tertiary care academic institute, Jodhpur. Samples N = 50 (25 + 25) were selected through consecutive sampling techniques and randomly assigned to intervention and control groups. The baseline data was collected with sample characteristics for both groups by using World Health Organisation Disability Assessment Schedule 2.0 to assess global functioning, the Medication Adherence Rating Scale for medication adherence. The community re-entry program group received 8 sessions of intervention each session is 45 minutes, and every day one session after post-intervention assessment and follow-up done at 1 month with the same scales. Statistical Package for Social Sciences (SPSS) version 20.0 was used. The data were analyzed using descriptive statistics (frequency, percentage, mean, and standard deviation) and inferential statistics Chi-square, fisher’s exact test and Yate’s correction used as applicable. Repeated measures-ANOVA mixed design (Two-way) is used for post-intervention comparison of outcome variables. Results: Post-intervention comparison of medication adherence, found that there was a significant time effect F = 566.406 and np2 = 0.922, group effect F = 24.495 and np2 = 0.338, interaction effect with large effect size F = 21.052 and np2 = 0.305. Whereas in global functioning there was a time effect with a large effect size of F = 65.783 and np2 = 0.578 but no group or interaction effect. Conclusion: CREP is effective in enhancing medication adherence in patients with bipolar affective disorder and consequently, useful for the treatment and prevention of symptoms recurrence.